(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Twitter, a popular social media platform, has become a rich source of user-generated content. The classification of Twitter users based on their characteristics and behavior has gained significant attention. Deep learning techniques, with their ability to capture complex patterns and representations, have emerged as powerful tools for Twitter user classification. This research article presents a compre hensive review of deep learning approaches for Twitter user classification. We discuss various deep learning architec tures, pretraining techniques, and transfer learning strategies used in the classification task. Through a thorough analysis of existing studies, we highlight the strengths and limitations of deep learning approaches and provide recommendations for future research in this field.